Change vegetation density analysis of Sumatran orangutan (Pongo abelii) habitat in Bukit Lawang and Sub-district of Bahorok. Issue 1 (February 2020) - Zaitunah, A; Ras, S; Samsuri
Abstract: Gunung Leuser National Park forest in Bukit Lawang section is the main habitat of Sumatran Orangutan ( Pongo abelii ) in Sub-district of Bahorok. The condition of wildlife habitat in the region has been fragmented by various human activities which is the major threat to the wildlife survival including Sumatran Orangutan ( Pongo abelii ). This study was conducted by overlaid some spatial data of the year 2008 and 2018 to obtain data of vegetation density changes and the range of the Normalized Difference Vegetation Index (NDVI) in Section of Bukit Lawang and District of Bahorok. Vegetation analysis was carried out in forest, rubber plantation and mix plantation in District of Bahorok as supporting data. The purposes of this study are to Get vegetation density value and analysing the changes of vegetation density of Sumatran Orangutan (P. abelii) habitat in Bukit Lawang and Sub-district of Bahorok year of 2018. The research shows that the largest vegetation density changes was decreased of high dense class which is 47, 040.02 hectare or 49.9%. The largest increased was occurred in the highest dense of 43, 304.1 hectare or 46.05%.